Nineteen new species of Megaselia Rondani (Diptera, Phoridae) from Denmark - Disney, R. Henry L; Bøggild, Esben (Zootaxa, 2021)
Nineteen new species, Megaselia culmenensis n. sp., M. cumrallum n. sp., M. dostrupensis n. sp., M. dravedskovensis n. sp., M. ehmsenae n. sp., M. falloclavis n. sp., M. fayesgadeensis n. sp., M. hobroensis n. sp.,M. hojerensis n. sp., M. jenshjerrildi n. sp., M. kajnisseni n. sp., M. micawberi n. sp., M. munki n. sp., M. neuter n. sp., M. onsildensis n. sp., M. romoensis n. sp., M. simestedensis n. sp., M. svendi n. sp., M. tofteensis n. sp. are described from Denmark. M. cumrallum is also reported from England. M. nigricia Disney & Durska reported from Denmark and its recognition clarified.